Synthesis of novel acridine bis-sulfonamides with effective inhibitory activity against the carbonic anhydrase isoforms I, II, IX and XII. Issue 20 (15th October 2015) - Esirden, İbrahim; Ulus, Ramazan; Aday, Burak; Tanç, Muhammet; Supuran, Claudiu T.; Kaya, Muharrem
Graphical abstract: Abstract: By using a multi component reaction system (MCR), nitro acridine sulfonamides were obtained from cyclic-1, 3-diketones, 4-aminobenzene sulfonamide and aromatic aldehydes. Some novel acridine bis-sulfonamides6a –l were then synthesized by the reaction between sulfonyl chlorides and the novel amino-acridine sulfonamides5a and5b, obtained by reduction of nitro-acridine sulfonamide derivatives4a and4b . The newly synthesized compounds were investigated as inhibitors of 4 human carbonic anhydrase isoforms (hCA, EC 4.2.1.1). Several of the compounds showed low micromolar inhibition against the medically relevant isoforms hCA I, II, IX, and XII.